2015
DOI: 10.1515/adms-2015-0020
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Young’s Modulus of the Porous Titanium Alloy with the Use of Fem Package

Abstract: Porous structures made of metal or biopolymers with a structure similar in shape and mechanical properties to human bone can easily be produced by stereolithographic techniques, e.g. selective laser melting (SLM). Numerical methods, like Finite Element Method (FEM) have great potential in testing new scaffold designs, according to their mechanical properties before manufacturing, i.e. strength or stiffness. An example of such designs are scaffolds used in biomedical applications, like in orthopedics' and mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…The mono-material Ti6Al4V structures were modelled as a linear elastic material (Ti6Al4V) with an elastic modulus of 110 GPa, a Poisson's ratio of 0.34 and density of 4500 kg/m³ [11,36]. The multi-material Ti6Al4V-PEEK structures were modelled, also, as a linear elastic material considering an elastic modulus of 3.76 GPa, a Poisson's ratio of 0.38 and a density of 1300 kg/m³ as PEEK properties [37].…”
Section: Numerical Analysis: Geometrical Model Boundary Conditions and Mesh Gridmentioning
confidence: 99%
“…The mono-material Ti6Al4V structures were modelled as a linear elastic material (Ti6Al4V) with an elastic modulus of 110 GPa, a Poisson's ratio of 0.34 and density of 4500 kg/m³ [11,36]. The multi-material Ti6Al4V-PEEK structures were modelled, also, as a linear elastic material considering an elastic modulus of 3.76 GPa, a Poisson's ratio of 0.38 and a density of 1300 kg/m³ as PEEK properties [37].…”
Section: Numerical Analysis: Geometrical Model Boundary Conditions and Mesh Gridmentioning
confidence: 99%
“…In a 2015 study by G. Rotta et al, it was demonstrated that SLM-printed porous Ti-6Al-4V had an 85% reduction in elastic modulus. The conventional alloy had a modulus of 110 GPa, while the 3D-printed porous Ti-6Al-4V showed a range of 17–49 GPa, which stands closer to actual human bone, varying from 0.15 to 18.1 GPa [ 127 ]. A study by Hasan et al suggests that shell thickness and porosity parameters for AM is also an important aspect for ensuring adequate mechanical properties [ 128 ].…”
Section: Metal-based Am With Added Functionalities and Applicationmentioning
confidence: 99%
“…In earlier days, bone defects were repaired using autografting from the cranium, tibia, rib, scapula, sternum, fascia, or ileum were used [ 126 ]. In later approaches, allografts (of cadaveric origin) and xenografts from animals were used for cranioplasty [ 127 , 128 ]. However, maintenance, revision surgery, and graft rejection are some of the problems with the above techniques [ 126 ].…”
Section: Metal-based Am With Added Functionalities and Applicationmentioning
confidence: 99%
“…Simplified models were considered for each structure typology and finite element meshes were generated using tetrahedral elements. The material of the structures was defined as linear elastic, Ti6Al4V with an elastic modulus of 110 GPa, a Poisson's ratio of 0.30 and density of 4500 kg/m 3 (Chen and Thouas, 2015;Rotta and Seramak, 2015). A load (F) was applied on the upper surface of the model and the elastic modulus (E) was estimated using the following expression:…”
Section: Mechanical Testing and Mechanical Modelingmentioning
confidence: 99%